Child Care Centers: Designing Spaces for Wellness and Development of Children - Akanksha Gupta; Deepti Pande Rana; Arun Kapur (International Journal of Children, 2024)
Hospital design has changed and evolved since the Modern Movement in architecture to meet the demands of the times. It is now believed to be dependent on several variables. An architect should design a space that promotes security and is advantageous to the patient. An inpatient's hospitalisation procedure is unavoidably stressful for them. For adults, the atmosphere of healthcare facilities matters a lot, but for paediatric patients, it matters much more. During a child's visit or stay, the architecture of healthcare facilities has a profound impact on their developing mind and body. Since youngsters want to investigate things up close and rely more on touch than adults do, great consideration should be paid to the kinds of materials utilised. Thus, at this stage, one of the most important variables is the materials utilised and how they are applied. The young patients have a variety of needs that must be met (psychological, physical, social, etc.), but the ultimate selection of these materials is also based on a set of priorities. The selection of materials and hues, which must also uphold the space's functionality and consistently support the patients' psychology, determines the space's ability to heal. This paper's goal is to list the cutting-edge materials utilised in contemporary children's healthcare facilities and assess how well they can meet the needs of the younger patients
Keywords: Children's healthcare; Design elements; children's healthcare technologies; family centric approach; materials and colours